Attitude of Primary School Teachers towards Inclusive Education - Singh, Richa; Bajpai, Amita (THE PRIMARY TEACHER, 2019)
Education is an essential building block of any civilisation. Today inclusive education is a widely accepted approach of the 21st century because it helps unfold the hidden potential of the students, ensures the rights of every individual without discrimination and creates a universal inclusive environment for the maximum development of children, as we all have equal rights despite many differences. Inclusive education fosters the idea of acceptance and promotes wider social acceptance, peace and cooperation. The purpose of the present study is to investigate the attitudes towards inclusive education among primary school teachers in Lucknow. The success of inclusive education depends on various factors, of which a teacher is the most important one. To become a competent and successful inclusive teacher, it is necessary to have the required knowledge, skills, democratic attitude, positive attitude and an attitude of collaboration and networking classroom. Therefore, to assist the regular education teacher, knowledge and understanding of their attitudes or perceptions towards inclusive education is critical. Hence, this study aims to find out the knowledge and attitude of primary school teachers towards inclusive education. The present study is a descriptive survey method and data has been analysed quantitatively. The study included a sample of 200 primary school teachers who were surveyed using a standardised tool. A total of 33 primary schools were randomly selected for this study (15 private primary schools and 18 government primary schools). The study assesses the attitude of primary school teachers towards inclusive education in relation to their gender and type of institute. The statistical technique of ‘t-test’ was used to analyse the attitudes towards inclusive education scores of private primary school teachers and government primary school teachers. The attitude of primary school teachers towards inclusive education may be influenced and developed within an educational system that can provide some specific conditions conducive to practice in this field.